Identification of a new molecular target of class IIa bacteriocins in Listeria monocytogenes EGDe - Calvez, S; Prévost, H; Drider, D (Folia microbiologica, 2008)
It was shown recently (Calvez et al. 2007) that glpQ and pde genes are involved in intermediate resistance of Enterococcus faecalis JH2-2 to DvnV41, a class IIa bacteriocin produced by Carnobacterium divergens V41. The listerial orthologs of lpQ and pde genes might be lmo0052 and lmo1292 genes, respectively. Here, the role of lmo0052 and lmo1292 genes in resistance of Listeria monocytogenes EGDe to DvnV41 and MesY105 was investigated. L. monocytogenes EGDe was inactivated in lmo0052 and/or lmo1292 by homologous recombination. Listerial mutant strain EGDSC02 (inactivated in the putative glpQ gene), was slightly resistant to DvnV41. The listerial mutant strain EGDSC01 (inactivated in the putative pde gene) remained, as the wild-type strain, sensitive to DvnV41, but was affected in growth parameters.
Keywords: mutace; bakteriální proteiny; Bacterial Proteins; fosfodiesterasy; Microbial Sensitivity Tests; Listeria monocytogenes; Bacteriocins; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents; Drug Resistance, Bacterial; bakteriociny; Mutation; Phosphoric Diester Hydrolases; bakteriální léková rezistence